Preparation method and application of green building wall thermal insulation material

By integrating microencapsulated phase change materials, intelligent adjustment layer and photocatalytic bioreaction layer, the shortcomings of existing green building wall insulation materials in terms of adaptability, functionality and environmental protection are solved, dynamic temperature adjustment, efficient insulation and versatility are achieved, and the energy efficiency and environmental protection performance of the building are improved.

CN119504174APending Publication Date: 2025-02-25范存园
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411375312.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-28
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

The existing green building wall insulation materials have shortcomings in adaptability, functionality and environmental protection, and are difficult to adapt to the dynamic changes in ambient temperature, and lack intelligent regulation capabilities and self-cleaning and air purification functions.

Method used

By integrating microencapsulated phase change materials, intelligent regulation layers and photocatalytic bioreaction layers, dynamic temperature regulation, efficient insulation, real-time monitoring and self-repair functions are achieved, while also having the capabilities of self-cleaning, air purification and additional thermal energy output.

Benefits of technology

It improves the insulation performance and energy efficiency of building materials, realizes real-time monitoring and adjustment of ambient temperature and humidity, and has self-repair, self-cleaning and air purification functions to meet the multiple needs of green buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119504174A_ABST
    Figure CN119504174A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of building material preparation, and discloses a preparation method and application of a green building wall thermal insulation material, and the preparation method comprises the following steps: taking pretreated bamboo fibers, cotton fibers and lignin as base materials, and carrying out physical treatment and chemical modification; the preparation method comprises the following steps: adding a nanoscale phase change material into a base material, and carrying out microencapsulation treatment on the base material; an intelligent adjusting layer is integrated in the material and comprises a sensing network and a self-repairing chemical agent; coating a photocatalytic layer on the surface of the material, and integrating a biological reaction layer; the multifunctional composite thermal insulation material is formed through a high-pressure lamination and gradient curing process, and the pretreatment comprises the step of cutting the bamboo fibers, the cotton fibers and the lignin until the length of the fibers is 5-20 mm. The microencapsulated phase change material, the intelligent adjusting layer and the photocatalytic biological reaction layer are integrated, the functions of dynamic temperature adjustment, efficient heat preservation, real-time monitoring, self-repairing, self-cleaning, air purification and heat energy output are achieved, and the building energy efficiency and the environmental protection performance are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of building material preparation, and in particular to a method for preparing a green building wall insulation material and application thereof. Background Art

[0002] The development of green building wall insulation materials is one of the important directions in today's construction field. As the global requirements for energy efficiency and environmental protection continue to increase, the role of insulation materials in construction is becoming more and more important. Through effective wall insulation materials, not only can the heat loss inside the building be reduced, but also the indoor temperature stability can be maintained under extreme climatic conditions, thereby greatly reducing the energy consumption of heating and cooling. Modern green buildings pursue energy saving, high efficiency and environmental protection. Therefore, high-quality insulation materials have become an indispensable part of green buildings.

[0003] Existing green building wall insulation materials usually use materials such as polystyrene (EPS), mineral wool board, foamed glass, etc. These materials prevent heat transfer through their own structure and material properties, thereby achieving insulation effect. For example, polystyrene material relies on its closed-cell structure to reduce air flow, and mineral wool board blocks heat conduction through its porous structure. These materials usually use low thermal conductivity as the main measurement indicator, which can achieve the purpose of reducing heat loss to a certain extent. In addition, such materials can also provide sound insulation function and improve the comfort of the building.

[0004] Although existing materials can reduce heat loss to a certain extent, there are still some shortcomings. First, the thermal insulation performance of traditional insulation materials relies on a single physical structure, which is difficult to adapt to the dynamic changes of ambient temperature and has limited thermal resistance. Especially when the temperature fluctuates greatly, the thermal insulation effect is poor. Secondly, such materials usually lack intelligent adjustment capabilities and cannot monitor and respond to ambient temperature and humidity in real time. They are prone to functional degradation during long-term use. Finally, the existing insulation materials have relatively single functions in environmental protection and lack the ability of self-cleaning, air purification or additional heat output. Summary of the invention

[0005] In view of the deficiencies in the prior art, the present invention provides a method for preparing a green building wall insulation material and its application. The present invention integrates microencapsulated phase change materials, an intelligent adjustment layer and a photocatalytic bioreaction layer to achieve dynamic temperature regulation, efficient insulation, real-time monitoring and self-repair functions. At the same time, it has the capabilities of self-cleaning, air purification and additional heat energy output, which solves the deficiencies of existing insulation materials in adaptability, functionality and environmental protection, and effectively improves the energy efficiency and environmental protection performance of buildings.

[0006] To achieve the above objectives, the present invention is implemented through the following technical solutions: A method for preparing a green building wall insulation material comprises the following steps:

[0007] By pre-treating bamboo fiber, cotton fiber and lignin as substrates, physical treatment and chemical modification were performed;

[0008] Add nano-scale phase change material to the substrate and perform microencapsulation treatment on it;

[0009] Integrate smart regulatory layers into materials, including sensing networks and self-healing chemistries;

[0010] Coating a photocatalytic layer on the surface of the material and integrating a bioreaction layer;

[0011] Multifunctional composite insulation material is formed through high pressure lamination and gradual curing process.

[0012] Preferably, the pretreatment comprises:

[0013] Cutting bamboo fiber, cotton fiber and lignin into fibers with a length of 5 to 20 mm and a diameter of 100 to 500 microns;

[0014] The fiber substrate is subjected to chemical modification treatment by using a silane coupling agent at a treatment concentration of 2% to 5% to improve its dispersibility and water resistance.

[0015] Preferably, the microencapsulation process comprises:

[0016] The nano-scale phase change material is microencapsulated by using polyvinyl alcohol and polymethyl methacrylate, the average diameter of the microcapsules is 100 to 300 microns, and the thickness of the microcapsule wall is 10 to 50 microns;

[0017] The encapsulated nano-scale phase change material is added to the substrate, and the mass ratio is controlled within 10% to 30% of the total mass of the substrate.

[0018] Preferably, the intelligent adjustment layer integration includes:

[0019] A sensor network made of carbon nanotubes is embedded in the material, with the distance between nodes being 5 to 10 cm, to achieve real-time monitoring of temperature and humidity;

[0020] Microencapsulated dimethicone is added as a self-healing agent, which releases the repair agent when the material is slightly damaged.

[0021] Preferably, the coating of the photocatalytic layer comprises:

[0022] The TiO2 nanoparticles doped with metal ions are coated on the surface of the material, and the average particle size of the particles is 20 to 50 nanometers;

[0023] The thickness of the coating layer is 0.1 to 0.5 mm to ensure the best photocatalytic effect under visible light conditions.

[0024] Preferably, the bioreaction layer integration includes:

[0025] Select anaerobic and photosynthetic bacteria that can operate stably under low temperature and pH changes;

[0026] The pH value and temperature of the bioreaction layer are controlled through an intelligent regulating layer to optimize the efficiency of heat energy generation.

[0027] Preferably, high pressure lamination comprises:

[0028] The lamination process is carried out under a pressure of 150 to 500 bar to ensure the close bonding of each functional layer;

[0029] The lamination time is 10 to 30 minutes, which is adjusted according to the thickness of the material and the required strength.

[0030] Preferably, the gradual curing process includes:

[0031] The temperature is gradually reduced from 180°C to room temperature. The entire curing process lasts for 6 to 12 hours.

[0032] By controlling the curing temperature and time, the interface bonding strength between the multi-layer materials is optimized.

[0033] The present invention also provides a green building wall insulation material, comprising:

[0034] The thermal resistance coefficient of this material is 0.4~0.5m 2 K / W;

[0035] The sound insulation performance of this material is 35-50dB;

[0036] The material has self-healing ability and can repair damage by releasing microencapsulated self-healing chemicals after micro-damage.

[0037] The present invention also provides the application of green building wall insulation materials, including: the material is used for building exterior walls, roofs and internal partition systems to provide insulation, sound insulation and environmental purification functions.

[0038] The present invention provides a preparation method and application of a green building wall insulation material, which has the following beneficial effects:

[0039] 1. The present invention integrates microencapsulated phase change materials to enable the material to efficiently store and release heat when the temperature changes, thereby improving the thermal insulation performance of the building material and making the thermal resistance coefficient of the material reach 0.4-0.5m 2 K / W can effectively reduce heat loss inside the building and ensure temperature stability, thereby reducing energy consumption and improving energy efficiency.

[0040] 2. The present invention realizes real-time monitoring and adjustment of temperature and humidity through the intelligent adjustment layer, ensuring that the material still has efficient thermal insulation performance in a complex environment. In addition, the self-repair function of the material automatically repairs micro-damages through microencapsulated dimethyl silicone oil, thereby enhancing the service life and long-term stability of the material.

[0041] 3. The present invention enables the material to have self-cleaning and air purification functions through the application of photocatalytic layer and biological reaction layer. While improving the quality of indoor and outdoor environment, it can also generate additional heat output through biological reaction, further improving the energy utilization rate and environmental protection of the material, and adapting to the multiple needs of green buildings. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 The figure is a flow chart of the method of the present invention. DETAILED DESCRIPTION

[0043] The following will be combined with the drawings in the specification of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0044] Please see attached Figure 1 The embodiment of the present invention provides a method for preparing a green building wall insulation material, comprising the following steps:

[0045] By pre-treating bamboo fiber, cotton fiber and lignin as the substrate, physical treatment and chemical modification are carried out. Physical treatment can reduce the agglomeration of fibers and ensure their uniform dispersion in subsequent processing; while chemical modification can change the polarity of the fiber surface, enhance the interfacial compatibility between the fiber and the substrate, and improve the overall strength and durability of the material. It not only maintains its natural light weight and high strength characteristics, but also makes it have better waterproofness and environmental adaptability, which is particularly suitable for the application scenarios of green building materials.

[0046] Nano-scale phase change materials are added to the substrate and microencapsulated. When the phase change temperature is reached, the phase change material absorbs and stores heat from the environment to lower the ambient temperature. When the temperature drops, the heat is released to maintain the temperature stability inside the building. The microencapsulation technology encapsulates the PCM through a polymer shell to prevent leakage or degradation during use, while enhancing its long-term performance and reducing the energy consumption of the building. It has a highly efficient energy-saving effect, especially under climate conditions with large seasonal temperature differences.

[0047] Integrate an intelligent adjustment layer into the material, including a sensor network and self-healing chemicals. The carbon nanotube sensor has extremely high sensitivity and can quickly capture small changes in temperature and humidity. The self-healing chemicals automatically repair small cracks in the material through chemical reactions to ensure the long-term use and performance stability of the material. The integration of the intelligent adjustment layer gives the material environmental self-adaptation ability, which can not only automatically adjust thermal resistance according to climatic conditions and improve energy efficiency, but also extend the service life of the material and reduce daily maintenance and replacement costs through self-healing technology;

[0048] A photocatalytic layer is coated on the surface of the material, and a bioreaction layer is integrated. The photocatalytic layer can decompose harmful gases and pollutants in the air under the action of sunlight, improving the air quality around the building. In addition, the layer also has a self-cleaning effect, reducing the maintenance requirements of the building's exterior walls, extending the service life of the exterior walls, and further reducing maintenance costs. The integrated bioreaction layer not only gives the material the ability to process waste, but also supplements the building's heating needs by decomposing the heat released by organic matter. This ecological cycle function effectively reduces the energy consumption of external heating and provides a self-sufficient heat source for the building system, further improving the overall energy efficiency of the building;

[0049] A multifunctional composite thermal insulation material is formed through high-pressure lamination and gradual curing process. The high-pressure lamination and gradual curing process ensures the close combination of different functional layers, improves the overall mechanical strength and stability of the material, and at the same time avoids the cracking or delamination phenomenon that is prone to occur in traditional materials when the interlayer bonding is not firm, thereby extending the service life of the material and ensuring the effectiveness of its long-term thermal insulation, sound insulation and intelligent adjustment functions.

[0050] Please see attached Figure 1 , the preprocessing includes:

[0051] Cut bamboo fiber, cotton fiber and lignin to a fiber length of 5 to 20 mm and a diameter of 100 to 500 microns. The length and diameter of the fiber affect the overall structural performance of the material and its ability to combine with other materials. By controlling the length and diameter of the fiber, its uniformity of dispersion in the composite material can be ensured, the structural stability of the composite material can be improved, and the overall strength and functionality of the material can be enhanced. By reasonably controlling the fiber length and diameter, the uniform distribution of the fiber can be ensured, the mechanical strength and durability of the material can be enhanced, and the bonding force between the fiber and other functional layer materials (such as nano phase change materials) can be improved, thereby improving the overall performance of the thermal insulation material;

[0052] The fiber substrate is chemically modified by using a silane coupling agent at a concentration of 2% to 5% to improve its dispersibility and water resistance. The silane coupling agent is a chemical substance that can form a chemical bridge between organic materials and inorganic materials. The mechanism of action of the silane coupling agent is to react with the hydroxyl groups of the fiber material through its active groups to form chemical bonds. This chemical reaction can enhance the surface energy of the fiber, making it easier to combine with other functional layers (such as nano PCM, photocatalytic layer) in other composite materials, thereby improving the mechanical properties and environmental stability of the overall material. In addition, the silane coupling agent can also give the fiber hydrophobic properties and improve its moisture resistance. By using a silane coupling agent at a concentration of 2% to 5% to chemically modify the fiber, the dispersibility and water resistance of the fiber can be effectively improved, the bonding force between the fiber and subsequent materials can be enhanced, and the durability, mechanical strength and water resistance of the entire composite thermal insulation material can be improved.

[0053] Please see attached Figure 1 , microencapsulation treatment includes:

[0054] The nano-scale phase change material is microencapsulated using polyvinyl alcohol and polymethyl methacrylate. The average diameter of the microcapsules is 100 to 300 microns, and the thickness of the microcapsule wall is 10 to 50 microns. Polyvinyl alcohol is a material with good biodegradability and waterproof properties, which can provide basic physical protection for the phase change material. Polymethyl methacrylate is a high-strength and durable polymer material that can enhance the mechanical strength of the microcapsules and has excellent UV resistance and weather resistance, ensuring that the microcapsules can remain stable after long-term exposure to the external environment. Through the dual encapsulation of polyvinyl alcohol and polymethyl methacrylate, the phase change material can maintain its excellent heat storage function while having better protection performance, extending its service life and improving its uniform distribution in the substrate. In addition, the diameter of the microcapsule (100 to 300 microns) optimizes the thermal response speed of the material, enabling the material to quickly absorb or release heat, thereby effectively regulating the temperature changes of the building.

[0055] The encapsulated nano-scale phase change material is added to the substrate, and the mass ratio is controlled at 10% to 30% of the total mass of the substrate. The thickness of the microcapsule wall is controlled by adjusting the solution concentration and reaction time of polyvinyl alcohol and polymethyl methacrylate. The thickness of 10 to 50 microns can effectively prevent the leakage of the phase change material and ensure that the microcapsule does not break under mechanical impact or thermal stress. At the same time, the thin wall (about 10 microns) can improve the thermal conductivity of the phase change material and ensure the rapid transfer of heat; the thick wall (about 50 microns) can provide higher mechanical strength and durability, and is particularly suitable for use in long-term thermal cycles. By controlling the thickness of the microcapsule wall within the range of 10 to 50 microns, the present invention achieves long-term stability of the material in a high-intensity environment while taking into account the thermal response performance and mechanical protection of the phase change material. This structural design not only improves the thermal conductivity efficiency of the material, but also increases its durability, ensuring that the thermal insulation material can continue to provide a stable thermal insulation effect under various complex climatic conditions.

[0056] Please see attached Figure 1 , the intelligent adjustment layer integration includes:

[0057] A sensor network made of carbon nanotubes is embedded in the material, and the distance between nodes is 5 to 10 cm to achieve real-time monitoring of temperature and humidity. The carbon nanotube sensor network consists of a series of sensor nodes, which are interconnected through highly conductive carbon nanotubes to form a distributed sensing system. The distance between the sensor nodes is designed to be 5 to 10 cm to ensure coverage of the entire material area and achieve comprehensive and real-time monitoring. The conductivity of carbon nanotubes is very sensitive to changes in temperature and humidity. When the temperature or humidity in the material changes, the resistance value of the carbon nanotubes also changes accordingly. Through real-time monitoring of resistance, the sensor network can accurately sense environmental changes and feed this information back to the central control system or regulator for corresponding adjustments. This function not only helps to maintain a comfortable environment inside the building, but also optimizes the insulation effect and reduces energy consumption by automatically adjusting the material performance. In addition, the flexibility and high durability of the carbon nanotube sensor network ensure the reliability and intelligence level of the material in long-term use.

[0058] Microencapsulated dimethicone is added as a self-healing agent, which releases the repair agent when the material is slightly damaged. The self-healing agent dimethicone is encapsulated through microencapsulation technology to form microcapsules with a diameter of 10 to 100 microns. Dimethicone has good fluidity and chemical inertness. When the material is microcracked, the microcapsules rupture, and the silicone oil flows out and fills the cracks. Under the action of air or moisture, the dimethicone will undergo a cross-linking reaction and solidify into a high-strength elastic polymer, thereby restoring the mechanical properties of the material. The self-healing function enables the material to cope with wear, microcracks and environmental stresses in the long-term use of buildings, reducing the cost of maintenance and replacement, while ensuring that the thermal insulation, sound insulation and other properties of the material are not affected by damage.

[0059] Please see attached Figure 1 , the coating of the photocatalytic layer comprises:

[0060] TiO2 nanoparticles doped with metal ions are coated on the surface of the material, and the average particle size of the particles is 20 to 50 nanometers. As a wide-bandgap semiconductor, the photocatalytic effect of TiO2 comes from the fact that when light is irradiated, electrons jump from the valence band to the conduction band to form electron-hole pairs. The doping of metal ions can reduce the light energy required for this energy transition, thereby exciting electron-hole pairs under visible light conditions and improving its photocatalytic activity. The introduction of TiO2 nanoparticles doped with metal ions enhances the photocatalytic activity of the thermal insulation material under visible light conditions. Compared with traditional TiO2 materials that rely on ultraviolet rays, the doping treatment enables the material to work efficiently under natural light conditions, decompose harmful substances and keep the surface of the material clean, thereby improving the material's air purification ability and self-cleaning performance;

[0061] The thickness of the coating layer is 0.1 to 0.5 mm to ensure the best photocatalytic effect under visible light conditions. The prepared metal-doped TiO2 nanoparticles are suspended in a dispersion liquid, and the nanoparticles are evenly coated on the surface of the insulation material by spraying, brushing or dipping. The thickness of the coating directly affects the light transmission and catalytic efficiency. A thinner coating (about 0.1 mm) can ensure that the depth of the light transmission layer is increased, and more TiO2 surfaces are excited by light, but the catalytic efficiency is lower; although a thicker coating (about 0.5 mm) provides more photocatalytic active sites, an overly thick coating may lead to uneven light absorption and reduce the photocatalytic efficiency. Therefore, a coating thickness range of 0.1 to 0.5 mm ensures the optimal coverage of the photocatalyst. The appropriate thickness of the coating can not only give full play to the photocatalytic performance of TiO2, effectively decompose organic pollutants in the air, and improve indoor air quality, but also maintain the mechanical strength and surface durability of the material, avoiding performance loss caused by too thin or too thick coatings.

[0062] Please see attached Figure 1 , the bio-reaction layer integration includes:

[0063] Select anaerobic bacteria and photosynthetic bacteria that can operate stably under low temperature and pH change conditions. Anaerobic bacteria and photosynthetic bacteria carry out degradation and metabolism of organic matter inside the material. Anaerobic bacteria ferment organic waste in an anaerobic environment to produce heat and some gaseous byproducts, especially under low temperature conditions. Photosynthetic bacteria use photosynthesis to decompose organic matter under weak light conditions and generate heat energy. The synergistic effect of the two can provide continuous heat output for the material under low temperature and changing pH conditions to ensure temperature control inside the material. By selecting anaerobic bacteria and photosynthetic bacteria, two types of microorganisms with strong adaptability and able to operate normally under low temperature and pH fluctuations, the stability and durability of the biological reaction layer are ensured. These microorganisms can still effectively generate heat when environmental conditions are unfavorable, which improves the material's ability to autonomously regulate temperature, reduces dependence on external energy, and improves the energy-saving effect of the building;

[0064] The pH value and temperature of the bioreaction layer are controlled by the intelligent regulating layer to optimize the efficiency of heat energy generation. The pH value and temperature of the bioreaction layer can be accurately monitored through the sensors and control systems in the intelligent regulating layer to ensure that the microorganisms can efficiently decompose organic matter in a suitable environment. The control of pH value can avoid the inhibitory effect of acidic or alkaline environment on microorganisms, while temperature regulation can ensure that the microorganisms maintain an efficient metabolic rate within the appropriate temperature range, thereby improving the efficiency of heat energy output, so that the bioreaction layer can operate for a long time under different climatic conditions and provide a stable supply of heat energy.

[0065] Please see attached Figure 1 , high pressure lamination includes:

[0066] The lamination process is carried out at a pressure of 150 to 500 bar to ensure the close combination of the functional layers. During the operation, the functional layers are stacked in a predetermined order and placed in a high-pressure lamination device for pressurization. The pressure is gradually increased to 150 to 500 bar through a multi-stage pressurization technology to ensure uniform force between the layers and avoid material deformation or damage caused by instantaneous pressurization. A flexible film or isolation plate is used to ensure uniform pressure distribution and prevent interlayer fracture caused by local overpressure. Through the high-pressure lamination process of 150 to 500 bar, the thermal insulation material of the present invention can achieve close combination of the functional layers and avoid the common delamination problem in traditional composite materials. This process greatly improves the mechanical strength and durability of the material, so that it maintains structural stability in long-term use and is not affected by changes in the external environment;

[0067] The lamination time is 10 to 30 minutes, which is adjusted according to the thickness of the material and the required strength. By controlling the lamination time within the range of 10 to 30 minutes, the lamination time can be flexibly adjusted according to the specific thickness of the material and application requirements to ensure that materials of different thicknesses and structures can be tightly combined under high pressure conditions. This control method makes the material more stable in structure and can effectively prevent interlayer detachment, bubble generation or functional layer damage, thereby improving the service life and safety performance of the material.

[0068] Please see attached Figure 1 , the gradual curing process includes:

[0069] The temperature is gradually reduced from 180°C to room temperature, and the entire curing process lasts for 6 to 12 hours. The temperature change during the curing process will cause thermal stress to be generated inside the material. In particular, in multi-layer composite materials, the thermal expansion coefficients of the materials of each layer are different, which is easy to generate interface stress. If the temperature drops too quickly, the material will not have time to release the internal thermal stress, which is easy to cause insufficient interface bonding strength between the layers, thereby causing delamination or microcracks. The gradual curing process allows the stress of each layer of material to be gradually released by slowly cooling, avoiding stress concentration and ensuring the interface bonding strength between the layers of material. By adopting a gradual curing process in which the temperature is gradually reduced from 180°C to room temperature, the present invention effectively prevents the interface stress concentration and delamination of the material during the rapid curing process, and improves the mechanical strength, fatigue resistance and service life of the material. In particular, during long-term use, the material can still maintain its excellent thermal insulation effect and structural integrity;

[0070] By controlling the curing temperature and time, the interface bonding strength between the multilayer materials is ensured to be optimal. By controlling the reasonable curing time (6 to 12 hours), the present invention ensures that the bonding between the multilayer materials is sufficient, and improves the interface bonding strength and mechanical properties of the materials. Whether it is a thinner thermal insulation material or a multilayer composite material with a complex structure, the curing reaction can be completed within this time range, thereby ensuring the performance and durability of the material.

[0071] The present invention also provides a green building wall insulation material, comprising:

[0072] The thermal resistance coefficient of this material is 0.4~0.5m 2 K / W;

[0073] The sound insulation performance of this material is 35-50dB;

[0074] The material has self-healing ability and can repair damage by releasing microencapsulated self-healing chemicals after micro-damage.

[0075] The present invention also provides the application of green building wall insulation materials, including: the material is used for building exterior walls, roofs and internal partition systems to provide insulation, sound insulation and environmental purification functions.

[0076] In order to better understand the present invention, the above contents are described in detail below in conjunction with specific embodiments.

[0077] Example 1: Standard green building wall insulation material

[0078] Material formula and process:

[0079] Base material: The fiber base material is made of bamboo fiber, cotton fiber and lignin, and is treated with a silane coupling agent to ensure it has good waterproofness and dispersibility.

[0080] Phase change material: microencapsulated paraffin phase change material, with a diameter of 100 to 300 microns, encapsulated in polyvinyl alcohol and polymethyl methacrylate shells, and the addition ratio is 20% of the total mass of the substrate.

[0081] Photocatalytic layer: It uses TiO2 nanoparticles doped with silver ions, with an average particle size of 30 nanometers and a coating thickness controlled at 0.3 mm to ensure self-cleaning and air purification functions.

[0082] Biological reaction layer: Integrates anaerobic bacteria and photosynthetic bacteria that can operate efficiently under low temperature and changing pH conditions. The intelligent adjustment layer monitors their operating status and maintains them under optimal temperature and pH conditions.

[0083] Smart Adjustment Layer: A carbon nanotube sensor network is embedded with a node spacing of 7 cm, which can monitor the temperature and humidity inside the material in real time and automatically adjust the material's performance to cope with environmental changes. Microencapsulated dimethicone self-healing agent is also evenly distributed in the material, ensuring that the material automatically repairs itself when it is slightly damaged.

[0084] Preparation process:

[0085] The substrate pretreatment, phase change material microencapsulation, photocatalytic layer coating and bioreaction layer integration are carried out according to the aforementioned method.

[0086] The various layers of material were compounded through a high-pressure lamination process (250 bar, lamination time 15 minutes) to ensure the bonding strength of each functional layer.

[0087] Using the gradual curing process, the temperature was gradually reduced from 180°C to 25°C, and the curing time was controlled to 10 hours.

[0088] Performance indicators:

[0089] Thermal resistance: 0.3m 2 K / W

[0090] Sound insulation performance: 40dB

[0091] Self-healing ability: After micro-damage, the microcapsules rupture, releasing dimethicone, and automatically heal the cracks within 24 hours.

[0092] Example 2: High-efficiency green building wall insulation material

[0093] Material formula and process:

[0094] Substrate: Bamboo fiber and lignin are the main substrates, treated with a higher concentration of silane coupling agent (5% concentration) to enhance their interfacial adhesion and durability.

[0095] Phase change material: fatty acid phase change material is used, the particle size after microencapsulation is 200-300 microns, and the addition ratio is 30% of the total mass of the substrate, which is used to provide better temperature regulation effect in areas with large temperature fluctuations.

[0096] Photocatalytic layer: TiO2 nanoparticles doped with copper ions, with a particle size of 25 nanometers and a coating thickness controlled at 0.4 mm. It is mainly used for efficient air purification and self-cleaning effects in strong light environments.

[0097] Biological reaction layer: The anaerobic bacteria population is enhanced, and the proportion of methane-producing bacteria is especially optimized to improve the efficiency of heat energy output in low temperature environments.

[0098] Intelligent regulation layer: The distance between sensor network nodes is shortened to 5 cm, ensuring more accurate environmental monitoring and regulation capabilities.

[0099] Preparation process:

[0100] The substrate is treated with a high concentration of silane coupling agent to enhance the adhesion between the substrate and other functional layers.

[0101] The fatty acid phase change material is encapsulated by microencapsulation technology and added into the substrate.

[0102] After the standard coating and integration process, the photocatalytic layer and the bioreaction layer were processed by high-pressure lamination, with the pressure set at 400 bar and the lamination time being 25 minutes.

[0103] A gradual curing process is used to reduce the temperature from 180°C to room temperature, with a curing time of 12 hours to ensure the molding of high-strength composite materials.

[0104] Performance indicators:

[0105] Thermal resistance: 0.5m 2 K / W

[0106] Sound insulation performance: 50dB

[0107] Self-healing ability: The material can automatically repair micro cracks within 12 hours.

[0108] Example 3: Lightweight green building wall insulation material

[0109] Material formula and process:

[0110] Substrate: Light natural fiber (such as straw fiber and flax fiber) is used as the main material, which is treated with silane coupling agent with a treatment concentration of 2%.

[0111] Phase change material: low-density organic ester phase change material is used. After microencapsulation, the diameter is controlled at 100 to 200 microns, and the addition ratio is 10% of the total mass of the substrate.

[0112] Photocatalytic layer: TiO2 nanoparticles doped with iron ions, with a particle size of 20 nanometers and a coating thickness controlled at 0.1 mm, used for self-cleaning and air purification in low-pollution environments.

[0113] Biological reaction layer: Integrates photosynthetic bacteria with strong adaptability to low temperatures to ensure that organic matter can still be degraded under low light conditions.

[0114] Smart regulation layer: A network of carbon nanotube sensors with 10 cm node spacing for basic temperature and humidity monitoring.

[0115] Preparation process:

[0116] The lightweight natural fibers are cut and chemically treated to ensure their dispersion and lightness.

[0117] The organic ester phase change material is encapsulated by microencapsulation technology and then added to the substrate. The added amount is low to maintain the lightweight structure of the material.

[0118] After the photocatalytic layer and the bioreaction layer are coated by standard process, a low-pressure lamination process of 150 bar is adopted, and the lamination time is 10 minutes.

[0119] A gradual curing process was used, with the temperature dropping from 180°C to 25°C over a curing time of six hours, ensuring the lightweight material retained its shape and structure during the curing process.

[0120] Performance indicators:

[0121] Thermal resistance: 0.2m 2 K / W

[0122] Sound insulation performance: 35dB

[0123] Self-healing ability: The material can repair mild micro-cracks within 24 hours.

[0124] Comparative experiment: thermal resistance performance test

[0125] Experimental purpose: To evaluate the thermal insulation effect of the green building wall thermal insulation material of the present invention.

[0126] Experimental setup

[0127] Experimental group (material of the present invention): The green building wall insulation material of the present invention is used, which has a composite insulation structure of phase change material microencapsulation, photocatalytic layer, intelligent adjustment layer and biological reaction layer.

[0128] Control group 1 (conventional polystyrene board material): polystyrene foam material, which is a common building insulation material on the market.

[0129] Control group 2 (traditional mineral wool board material): Mineral wool board is a common thermal insulation material with good thermal insulation and sound insulation properties.

[0130] Experimental procedures

[0131] Sample preparation:

[0132] Experimental group: Samples were prepared according to the method for preparing green building wall insulation materials of the present invention, with a thickness of 50 mm.

[0133] Control group 1: polystyrene board material, thickness of 50 mm.

[0134] Control group 2: traditional mineral wool board material, thickness of 50 mm.

[0135] Experimental equipment:

[0136] Heat flow meter thermal resistance tester;

[0137] Constant temperature box (used to control the experimental environment temperature).

[0138] Experimental environment settings:

[0139] The temperature inside the thermostat is set to 20°C to simulate the internal environment of common buildings;

[0140] The temperature difference on both sides of the test is 20℃, one side is 20℃ and the other side is 40℃, to simulate the use environment of the thermal insulation material.

[0141] Experimental process:

[0142] Each group of samples is placed in a heat flow meter for testing in turn, the heat flux density of the material is measured, and the steady-state thermal conductivity of the material is recorded;

[0143] Calculate the thermal resistance coefficient of each group of materials (thermal resistance R = material thickness / thermal conductivity);

[0144] Each group of samples was tested three times and the average value was taken.

[0145] The comparative experimental data are shown in Table 1:

[0146] Table 1 Thermal resistance performance test data table

[0147]

[0148] From the data in Table 1, we can get:

[0149] The average thermal resistance coefficient of the experimental group (material of the present invention) is 0.49m 2 K / W, which is significantly higher than the thermal resistance coefficients of control group 1 (polystyrene board) and control group 2 (mineral wool board), which are 0.30m 2 K / W and 0.34m 2 K / W, which indicates that the material of the present invention has better thermal insulation performance and can provide higher thermal resistance, thereby more effectively isolating heat energy and reducing heat energy loss.

[0150] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a green building wall insulation material, characterized in that: The following steps are involved: By pre-treating bamboo fiber, cotton fiber and lignin as substrates, physical treatment and chemical modification were performed; Add nano-scale phase change material to the substrate and perform microencapsulation treatment on it; Integrate smart regulatory layers into materials, including sensing networks and self-healing chemistries; Coating a photocatalytic layer on the surface of the material and integrating a biological reaction layer; Multifunctional composite insulation material is formed through high pressure lamination and gradual curing process.

2. The method for preparing green building wall insulation material according to claim 1, characterized in that: Preprocessing includes: Cutting bamboo fiber, cotton fiber and lignin into fibers with a length of 5 to 20 mm and a diameter of 100 to 500 microns; The fiber substrate is chemically modified by using a silane coupling agent at a concentration of 2% to 5% to improve its dispersibility and water resistance.

3. The method for preparing green building wall insulation material according to claim 1, characterized in that: Microencapsulation processing includes: The nano-scale phase change material is microencapsulated by using polyvinyl alcohol and polymethyl methacrylate, the average diameter of the microcapsules is 100 to 300 microns, and the thickness of the microcapsule wall is 10 to 50 microns; The encapsulated nano-scale phase change material is added to the substrate, and the mass ratio is controlled within 10% to 30% of the total mass of the substrate.

4. The method for preparing green building wall insulation material according to claim 1, characterized in that: Smart adjustment layer integration includes: A sensor network made of carbon nanotubes is embedded in the material, with the distance between nodes being 5 to 10 cm, to achieve real-time monitoring of temperature and humidity; Microencapsulated dimethicone is added as a self-healing agent, which releases the repair agent when the material is slightly damaged.

5. The method for preparing green building wall insulation material according to claim 1, characterized in that: The coating of the photocatalytic layer includes: The TiO2 nanoparticles doped with metal ions are coated on the surface of the material, and the average particle size of the particles is 20 to 50 nanometers; The thickness of the coating layer is 0.1 to 0.5 mm to ensure the best photocatalytic effect under visible light conditions.

6. The method for preparing green building wall insulation material according to claim 1, characterized in that: The bio-response layer integration includes: Select anaerobic and photosynthetic bacteria that can operate stably under low temperature and pH changes; The pH value and temperature of the bioreaction layer are controlled through an intelligent regulating layer to optimize the efficiency of heat energy generation.

7. The method for preparing green building wall insulation material according to claim 1, characterized in that: High pressure lamination includes: The lamination process is carried out under a pressure of 150 to 500 bar to ensure the close bonding of each functional layer; The lamination time is 10 to 30 minutes, which is adjusted according to the thickness of the material and the required strength.

8. The method for preparing green building wall insulation material according to claim 1, characterized in that: The gradient curing process includes: The temperature is gradually reduced from 180°C to room temperature. The entire curing process lasts for 6 to 12 hours. By controlling the curing temperature and time, the interface bonding strength between the multi-layer materials is optimized.

9. Green building wall insulation material, characterized in that: The method for preparing the green building wall insulation material according to any one of claims 1 to 8 comprises: The thermal resistance coefficient of this material is 0.4~0.5m 2 K / W; The sound insulation performance of this material is 35-50dB; The material has self-healing ability and can repair damage by releasing microencapsulated self-healing chemicals after micro-damage.

10. Application of green building wall insulation materials, characterized in that: The use of the green building wall insulation material described in claim 9 includes: the material is used for building exterior walls, roofs and internal partition systems to provide insulation, sound insulation and environmental purification functions.

Citation Information

Patent Citations

  • Phase-change thermal-storage intelligent temperature-control wall material and preparation method thereof

    CN102992703A

  • Preparation method of biomass-based temperature control material and prepared temperature control material

    CN112940688A

  • Composite material-concrete interface monitoring method based on carbon nanotube filling interface

    CN116165251A